LANGUAGE USE IN PUBLIC SPACE (LINGUISTIC LANDSCAPE STUDY IN SHOPPING CENTERS IN MAKASSAR CITY) - Syamsurijal Syamsurijal; Ery Iswary (International Journal of Social Science, 2023)
The purpose of this research is; 1) describe the linguistic landscape used in the Makassar City shopping center; 2) describe the dominant use of language in the linguistic landscape; and 3) knowing the reasons for using foreign languages in the linguistic landscape in shopping centers in Makassar. This research is a qualitative research designed descriptively. The locus of this research was in three shopping centers in Makassar City, namely Panakukang Mall, Nipah Mall and Ratu Indah Mall. Data is collected through documentation techniques. Analysis was carried out using qualitative techniques through data collection procedures, data reduction, data presentation, and conclusion/verification. The results of the study show that the types of landscapes found in shopping centers in Makassar City are top-down and bottom-up linguistic landscapes. The bottom-up landscape type is dominant in shopping centers in Makassar. In addition, foreign languages, especially English dominate the linguistic landscape in shopping centers in Makassar City. This is motivated by several factors, self-image (business image) and efforts to strengthen brand makers as an attraction for consumers